Biological responses of Chironomus sancticaroli to exposure to naturally aged PP microplastics under realistic concentrations - Rani-Borges, Bárbara; Queiroz, Lucas Gonçalves; Prado, Caio César Achiles; de Moraes, Beatriz Rocha; Ando, Rômulo Augusto; de Paiva, Teresa Cristina Brazil; Pompêo, Marcelo (Ecotoxicology (London), 2023)
Microplastic (MP) is yet another form of chronic anthropogenic contribution to the environment. MPs are plastic particles (<5 mm) that have been widely found in the most diverse natural environments, but their real impacts on ecosystems are still under investigation. Here, we studied the toxicity of naturally aged secondary polypropylene (PP) MPs after constant exposure to ultraviolet radiation (26 µm) to the third instar larvae of Chironomus sancticaroli , a dipteran species. The concentrations tested were 13.5; 67.5; and 135 items g −1 of dry sediment. C. sancticaroli organisms were investigated for fragment ingestion, mortality and changes in enzymatic biomarkers after 144 h of exposure. The organisms were able to ingest MPs from the first 48 h, and the amount of items internalized was dose-dependent and time-dependent. Overall, the results show that mortality was low, being significant at the lowest and highest concentrations (13.5 and 135 items g −1 ). Regarding changes in biochemical markers, after 144 h MDA and CAT activities were both significantly altered (increased and reduced, respectively), while SOD and GST levels were unchanged. In the present study, naturally aged polypropylene MPs induced biochemical toxicity in C. sancticaroli larvae, with toxicity being higher according to exposure time and particle concentration.